Jennifer Brennan: Tradewinds & Coconuts. A Reminiscence & Recipes from the Pacific Islands - L, R W (Petits Propos Culinaires, 2024)
Jennifer Brennan: Tradewinds & Coconuts. A Reminiscence & Recipes from the Pacific Islands: Periplus, Boston, 2000: ISBN 962-593-819-2: 304 pp., illustrated by author, recipe directory, glossary, bibliography, general and culinary index, menu suggestions, h/b, 34.95.